Slaughterhouse-five : or, The children's crusade, a duty -dance with death - Vonnegut, Kurt. ([New York] : Delacorte Press, 1969)
A chaplain's assistant, who was a World War II POW, is unstuck in time, living alternately in the past, the future, on Earth and on Tralfamadore.
"A Seymour Lawrence book."
Keywords: World War, 1939-1945 -- Fiction; Historical fiction; Science fiction; War stories